146k views
1 vote
Given f(x) and g(x)=k*f(x)

Given f(x) and g(x)=k*f(x)-example-1

1 Answer

6 votes

Answer:

k = -3

Explanation:

f(x) has a slope of 1, and g(x) has a slope of -3, so to get to g(x) from f(x) you would have to multiply it by -3. We need to check the true functions to be sure, though.

The true function for f(x) is f(x) = x + 4.

The true function for g(x) is g(x) = -3x - 12.

g(x) = -3*f(x)

User Gps
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.